Perioperative outcomes of esophagectomy after doublet versus docetaxel‐based triplet neoadjuvant chemotherapy in older patients: A nationwide inpatient database study in Japan - Yuki Hirano; Takaaki Konishi; Hidehiro Kaneko; Satoru Matsuda; Hirofumi Kawakubo; Yuya Kimura; Hiroki Matsui; Kiyohide Fushimi; Hiroyuki Daiko; Osamu Itano; Hideo Yasunaga; Yuko Kitagawa (Annals of Gastroenterological Surgery)
Abstract Background Although docetaxel‐based triplet neoadjuvant chemotherapy has yielded promising results for locally advanced esophageal cancer, there are concerns that the triplet regimen can increase perioperative adverse events in older patients. This retrospective study assessed the perioperative outcomes following doublet or docetaxel‐based triplet chemotherapy and esophagectomy in older patients. Methods The data of patients aged 70–79 years who received cisplatin and 5‐fluorouracil (CF) or docetaxel, cisplatin, and 5‐fluorouracil (DCF) before esophagectomy were extracted from a nationwide Japanese inpatient database (April 2012–March 2022). The primary outcomes were major and respiratory complications. The secondary outcomes included anastomotic leakage, 30‐day unplanned readmission, and 30‐ and 90‐day mortality. Analyses were conducted using overlap propensity score weighting, propensity score matching, and instrumental variable methods to adjust for potential confounders. Results Of 5229 eligible patients, 3457 (66%) and 1772 (34%) patients received neoadjuvant CF and DCF, respectively. Major and respiratory complications occurred in 5229 (40%) and 1388 (27%) patients, respectively. After overlap weighting, DCF was not associated with a higher frequency of major (odds ratio 0.99 [95% confidence interval 0.87–1.12]) and respiratory complications (odds ratio 1.04 [0.90–1.19]) compared with CF. The frequencies of anastomotic leakage, 30‐day unplanned readmission, and 30‐ and 90‐day mortality did not differ between the groups. Propensity score matching and instrumental variable analyses yielded similar results. Conclusions Neoadjuvant DCF was not associated with a higher frequency of perioperative adverse events compared with CF after esophagectomy in patients aged 70–79 years.